Multiple Alloantibodies Induced Autoimmune Hemolytic Anemia in Beta Thalassemia Woman with Megaloblastic Anemia during Pregnancy: A Case Report and Literature Review - Ye, Shiguang; Pan, Mengmeng; Zhou, Lili; Li, Ping; Wang, Xiuqin; Liang, Aibin (Archives of Clinical and Medical Case Reports, 2019)
Thalassemia is prevalent in Southern China and pregnancy with thalassemia becomes not rare in this area. Due to the unique pathophysiologic mechanism, pregnant complications in beta thalassemia are more complicated than normal pregnancy, such as hypercoagulation state, infant intrauterine growth restriction, impaired heart function and anemia. Despite of these, the clinical outcome of beta thalassemia pregnancy has been reported better currently. In this article, we report one interesting and distinct case of beta thalassemia pregnancy with complicated anemia. A pregnant woman, with beta thalassemia intermedia and underlying megaloblastic anemia, suffers the complex autoimmune hemolytic anemia after delivery. Screening for antibodies identifies two alloantibodies, anti-E IgG and anti-Lea IgM antibodies, which both contribute to the autoimmune hemolytic anemia. Glucocorticoid combined with immunoglobin has a good response and warm blood transfusion is also important in the treatment.